PENGARUH UKURAN PARTIKEL DAN KOMPOSISI ABU SEKAM PADI HITAM TERHADAP SIFAT KEKUATAN TARIK KOMPOSIT POLIESTER TIDAK JENUH - Rotua Adryani, Maulida (Jurnal Teknik Kimia USU, 2014)
This research was aimed to investigate the effect of black rice husk ash particle size and black rice husk ash composition as filler in tensile strength of unsaturated polyester composites. The composites were made with open mixing method by mixing unsaturated polyester with black rice husk ash with particle size variation of 100 mesh and 250 mesh, and volume fraction ratio between filler and matrix 95/5 : 90/10 : 85/15 : 80/20 then added with 1% methyl ethyl ketone peroxide as catalizer into mixture of unsaturated polyester and black rice husk ash. Tests performed are tensile, elongation at break, and Young’s modulus. The result of obtained at a ratio 95/5 with a particle size of 100 and 250 mesh was 24,413 MPa and 24,689 MPa.